Critical and Analytical Thinking about Controversial Issues in Digital Historical Sources - Intan Permana Sari; Ipong Jazimah (Proceedings Series on Social Sciences & Humanities, 2026)
This article discusses the ability to think critically and analytically about controversial issues in digital historical sources. History writing in the digital era is growing with the existence of digital historical sources. Digitization allows for wider access to historical information that is rarely known or even recorded in print historical sources. Through digital historical sources, the digitization ability of people from various walks of life plays an important role in improving their critical and analytical thinking skills in studying controversial issues circulating in digital historical sources. The method used in compiling this article is the literature study method where researchers obtain reference sources from libraries and mobile libraries. Historians study a historical event using various historical sources such as printed, oral, and digital sources. Each of these types of historical sources has its level of credit worthiness. The use of digital historical sources is one of the important factors to help researchers write the narrative of a historical event. Therefore, in examining controversial issues circulating in digital history sources, the role of individuals from various circles is very important in criticizing and analyzing controversial issues that are widely circulated. Freedom in accessing information through digital allows researchers, academics, or the general public to know historical facts that are rarely known. As this study is a literature review, explicitly indicate the findings based on the reviewed literature, include identified themes based on the library research, write potential implications.